The influence of interpersonal skills on professional success in performance athletes - Calin, M. F.; Mihai, R. A. (Science, Movement & Health, 2018)
Problem statement. Sports life is full of trials, the moments of tension that a performance sportsman needs to invest and master to achieve positive results. Based on each person's skills, motivation, and values that each person can promote can make professional athletes' success Purpose of study: 1. It is presumed that there is a positive correlation between professional recognition and interpersonal skills of high school students; 2. It is presumed that there is a positive correlation between the desire to challenge and leadership. Research methods. The research was based on three surveys that have aimed to identifyn on-cognitive skills, value questionnaire and motivational dominant questionnaire. Respondents were instructed to complete the questionnaires appropriately to situations most frequently encountered in every day life. Findings. To validate the hypothesis we used pearson correlations on a sample of 33 performance athletes, 15- to 17-year-old high school students from the 9th and 10th grades. Conclusions.The results of the study show that there is a positive correlation between the desire to challenge and the leadership ability and between professional recognition and interpersonal skills in the sense that people who are recognized as sporting achievements have developed and the interpersonal skills through which they successfully carry out the tasks they have received. The desire for increased challenge leads to a good leadership ability, the individual being able to guide, encourage and support the members of the group in the sports activities unfolded.